Plan de incentivos para mejorar la productividad de la fuerza de ventas de la empresa People Outsourcing S.A.C. sucursal Trujillo 2016 - Zelada Villanueva, Robinson Alonso (2016)
The present investigation takes as a purpose to know the situation for which it crosses the force of sales of the company “People Outsourcing S.A.C” and to propose alternatives that allow him to generate value. On the problem: Of what way an incentives plan, does division allow to improve the productivity of the force of sales of the company “People Outsourcing S.A.C” Trujillo?, with big help of the investigated theoretical frame and applying personal survey as skill of compilation of information, directed to 26 hard- working representatives of the force of sale, it was possible to raise the necessary information to know about the topic and the problematic reality. Based on the obtained results I conclude: The company “People Outsourcing S.A.C.” from the year 2013, it confronts a constant decrease in the productivity of the force of sales. The account "inmobiliaria" of the client “Centenary S.A.C.” it is the one that major decreasing index presents from 39 % to 23 %. In question to the most important factor for the development of the force of sales we have: “Salary“ and “Incentives“ with 38. 5 % and 23. 1 % respectively. Finally fulfilling the main objective of this research available to let " People Outsourcing S.A.C. " adequate incentive plan, focused on the needs of the sales force and the company